PORTFOLIO - Alimova Xayriniso Saidakbar qizi; Aktamxonova Nozimabonu Abrorjon qizi (Ustozlar uchun, 2023)
A portfolio is a purposeful collection or compilation of works, artifacts, or evidence that showcases a person's skills, achievements, growth, and learning progress. It is commonly used in educational settings, professional fields, or creative industries to provide a comprehensive view of an individual's abilities and accomplishments.